The effect of oxidation and reduction processes of graphite on physicochemical properties of graphite oxide and reduced graphene oxide - Drewniak, Sabina; Pustelny, Tadeusz; Muzyka, Roksana; Konieczny, Grzegorz; Kałużyński, Piotr (Photonics Letters of Poland, 2014)
Graphite oxide (GrO) and reduced graphene oxide (RGO) due to the sensitivity of their physical properties to the selected gases can be used in optical gas sensors. Sensor properties of GrO and RGO dependent significantly on the technology used for their production. In this paper the effect of the processes of oxidation and reduction of graphite on the physicochemical properties were presented. Full Text: PDF References U. Lange, T. Hirsch, V. M. Mirsky, O. S. Wolfbeis, "Hydrogen sensor based on a graphene – palladium nanocomposite", Electrochimica Acta 56 3707 (2011) CrossRef B. H. Chu, C. F. Lo, J. Nicolosi, C. Y. Chang, V. Chen, W. Strupiński, S. J. Pearton, F. Ren, "Hydrogen detection using platinum coated graphene grown on SiC", Sensors and Actuators B, 157 500 (2011) CrossRef L. Ganhua, E. O. Leonidas, C. Junhong, "Gas detection using low-temperature reduced graphene oxide sheets", App. Phys. Lett. 94 083111 (2009) CrossRef Botas C, Alvarez P, Blanco C, Santamaria R, Granda M, Ares P, Rodriguez Reinoso F, Menendez R., "The effect of the parent graphite on the structure of graphene oxide", Carbon; 50 257 2012 CrossRef Sun L, Fugetsu B., "Mass production of graphene oxide from expanded graphite", Materials Letters, 109 207 (2013). CrossRef Goers D, Spahr MS, Leone A, Markle W, Novak P., "The influence of the local current density on the electrochemical exfoliation of graphite in lithium-ion battery negative electrodes", Electrochimica Acta 56 3799 (2011) CrossRef J. I. Paredes, S. Villar-rodil, M. J. Fernández-Merino, L. Guardia, A. Martínez Alonso, J. M. D. Tascón, "Environmentally friendly approaches toward the mass production of processable graphene from graphite oxide", Journal of Materials Chemistry 21, 298 (2011) CrossRef M. H. Tran, C. S. Yang, S. Yang, I. J. Kim, H. K. Jeong., "Influence of graphite size on the synthesis and reduction of graphite oxides", Current Applied Physics 14, 74 (2013) CrossRef T. Pustelny, M. Procek, E. Maciak, A. Stolarczyl, S. Drewniak, M. Urbańczyk, M. Setkiewicz, K. Gut, Z. Opilski, "Gas sensors based on nanostructures of semiconductors ZnO and TiO2", Bull. Pol. Ac.: Tech. 64, 4 (2012) CrossRef T. Pustelny, M. Setkiewicz, S. Drewniak, E. Maciak, A. Stolarczyk, M. Procek, M. Urbańczk, K. Gut, Z. Opilski, I. Pasternak, W. Strupiński, "The Influence of Humidity on the Resistance Structures with Graphene Sensor Layer", Acta Phys. Pol. A 122, 5 (2012) DirectLink Ł. Smędowski, R. Muzyka, "Grafen – metody otrzymywania a zastosowanie i właściwości", Karbo 2, 128 (2013)- in polish Patent US 2798878. DirectLink B. Kwiecińska, H. Petersen, "Graphite, semi-graphite, natural coke, and natural char classification—ICCP system", International Journal of Coal Geology 57 99 (2004) CrossRef Z.Q. Li, C.J. Lu, Z. P. Xia, Y. Zhou, Z. Luo, "X-ray diffraction patterns of graphite and turbostratic carbon", Carbon 45 1686 (2007) CrossRef Z. Gao, H. Jin, X. Li, Z. Hua, "Phase Transformation Mechanism of Graphite-Turbostratic Graphite in the Course of Mechanical Grinding", Chem. Res. Chinese u. 19 216 (2003) DirectLink